A Review on Green Synthesis of Silver Nanoparticles Using Plant Extracts and Their Antibacterial Properties - Wayan Gracias; Indah Miftakhul Janah (Justek : Jurnal Sains dan Teknologi, 2026)
The escalating challenge of antimicrobial resistance (AMR) has prompted growing scientific attention toward plant-assisted green synthesis of silver nanoparticles (AgNPs) as a sustainable source of antimicrobial materials. This literature review synthesizes findings from 32 peer-reviewed studies published between 2020 and 2026, encompassing more than 32 plant species across 14 countries, to examine how synthesis conditions influence physicochemical characteristics and in vitro antibacterial activity. The reviewed studies indicate that AgNPs formation and performance are shaped more by synthesis parameters than by plant identity itself. The most favorable conditions were generally AgNO₃ concentrations of 1–3 mM, temperatures of 45–75 °C, pH 7–9, extract-to-precursor ratios of 1:9 to 2:1, and reaction times of 30–60 minutes in aqueous systems, typically yielding spherical nanoparticles of 10–30 nm. Smaller particles often showed stronger antibacterial effects, although colloidal stability remained an important determinant of performance. Among the reported systems, Azadirachta indica-derived AgNPs showed the strongest antibacterial activity. Overall, the evidence suggests that plant-based AgNP synthesis is a promising and environmentally benign approach, while methodological standardization and broader testing against resistant pathogens remain necessary for more reliable comparison and future application.